Million dollar micro business : how to turn your expertise into a digital online course - Tower, Tina (John Wiley & Sons Australia, Ltd., 2021)
"Million Dollar Micro Business is a book for the modern entrepreneur. The traditional way of doing business with large companies and even bigger overheads is gone. There's a new, smarter way to do business which give us the opportunity to create a greater impact, with less resources. There's no massive investment or business loans required to start a million dollar micro business, just your expertise, packaged, to share with the world. Million Dollar Micro Business is for people who know deep down that there's a better life waiting for them than slogging it away in traditional workplaces for another few decades. Many people now days have heard of online courses and membership businesses but they don't know where to start or what's really possible. Million Dollar Micro Business is a tangible guide book in getting started, featuring a framework and case studies of people who have previously started and scaled million dollar online information businesses"--